Protective Role of Rosmarinic Acid in Experimental Urolithiasis: Understanding Its Impact on Renal Parameters - Anelise Felício Macarini; Luísa Nathalia Bolda Mariano; Mariana Zanovello; Rita de Cássia Vilhena da Silva; Rogério Corrêa; Priscila de Souza (MDPI AG, 2024)
This study aimed to assess the ability of rosmarinic acid (RA) to prevent kidney stone formation in an ethylene glycol and ammonium chloride (EG/AC) model. There was an increase in diuresis in the normotensive (NTRs) and hypertensive rats (SHRs) treated with hydrochlorothiazide (HCTZ) and exposed to EG/AC, while RA restored urine volume in NTRs. The EG/AC groups exhibited lower urine pH and electrolyte imbalance; these parameters were not affected by any of the treatments. Both HCTZ+EG/AC and RA+EG/AC reduced calcium oxalate crystal formation in NTR and SHR urine. Kidney tissue analysis revealed alterations in oxidative stress and inflammation parameters in all EG/AC-receiving groups, with RA enhancing antioxidant defenses in SHRs. Additionally, crystals were found in the kidney histology of all EG/AC-exposed groups, with reduced Bowman's capsule areas in NTRs and SHRs. The NTR VEH+EG/AC group showed intense renal damage, while the others maintained their structures, where treatments with HCTZ and RA were fundamental for kidney protection in the NTRs. Docking analysis showed that RA exhibited good binding affinity with matrix metalloproteinase-9, phosphoethanolamine cytidylyltransferase, and human glycolate oxidase enzymes. The data disclosed herein underscore the importance of further research to understand the underlying mechanisms better and validate the potential of RA for clinical use.